Vector-valued partial differential equations and applications : Cetraro, Italy 2013 /: Cetraro, Italy 2013. (2017) - Dacorogna, Bernard, 1953-; Fusco, Nicola, 1956-; (Mathematician), Müller, Stefan; Sverak, Vladimir
No abstract available